Impact of the COVID-19 pandemic on the budget of Slovak local governments: Much cry and little wool? - Tomáš Černěnko; Erika Neubauerová; Alena Zubaľová (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2021)
The aim of the paper is to examine the impact of the COVID-19 pandemic on the budgets of Slovak local governments and to propose measures that would help them better cope with similar shocks in the future (in the economic context). In the first step, we compare tax revenues with their forecast values from 2019. Subsequently, we focus on the dependence of local government revenues on share taxes - personal income tax, which we examine using the Herfindahl-Hirschman Index at the level of individual local governments. We then examine this in the context of size categories of local governments as well as physical space - regions and districts. The results suggest that the COVID-19 impact on local government revenues was much less than expected. However, it revealed the economic limits of the system (structure) of local self-government in Slovakia with a majority of small (and vulnerable) local governments. The way out would be a shift to property taxes, but this is limited due the reluctance of local government representatives to accept a greater degree of responsibility for filling the revenue side of budgets with local taxes and fees.
Keywords: H24; H30; H71; 330; Herfindahl-Hirschman Index; Shared Taxes; Tax Income Concentration; Local Taxes And Fees; Covid-19; Local Government